Explaining the negative impact of financial concern on undergraduates' academic outcomes: evidence for stress and belonging as mediators. Issue 9 (20th October 2020) - Reid, Matthew; Jessop, Donna C.; Miles, Eleanor
ABSTRACT: Poorer financial circumstances among undergraduate students predict worse academic outcomes, yet there is a lack of research examining mediators. Accordingly, the present research aimed to identify such mediating variables. In Study 1, cross-sectional data were collected from UK undergraduates ( N = 516). Controlling for background variables, path analysis indicated that stress, sense of belonging at university, working memory, and self-control mediated the negative relationship between financial concern and academic performance. In Study 2 an independent sample ( N = 2794) was used to successfully validate the respecified model developed in Study 1. Additionally, longitudinal data were collected from UK undergraduates ( N = 453) at three time points in an academic year. Controlling for background variables, financial concern predicted subsequent changes in intrinsic academic motivation, as mediated by changes in stress and sense of belonging at university. Together, this provides consistent evidence for stress and belonging as mediators of the impact of finances on academic outcomes. Our findings afford a more complete understanding of how financial concern may affect students' experience at university, highlight potential negative consequences of funding systems that place a financial burden on students, and could serve to inform interventions aimed at mitigating the negative effects of financial concern.